Improving Learning Outcomes in Theme 3 My Daily Tasks for Class II Students through the Kahoot Application - Fajar Syahru Romadhon (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve thematic learning outcomes through the Kahoot application. This research is a classroom action research (PTK) which was conducted in 3 cycles. The research was conducted in three cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. This research was conducted on second grade students at SD Negeri Margasari 03, Margasari District, Tegal Regency with a total of 29 students. Research time was conducted from October to November 2020. The data collection technique used tests. Data analysis consisted of data reduction, data presentation, and conclusion drawing. Research shows the use of the Kahoot application can improve the learning outcomes of the theme 3 of my daily tasks in class II SD Negeri Margasari 03 Academic Year 2020/2021 as evidenced by the percentage of completeness of learning outcomes in cycle I, namely 76%, in cycle II it increases to 83% and cycle III to 90%.